Evaluation of Soft Tissue Calcifications in the Head and Neck Region on Panoramic Radiography of Edentulous Patients - Duran, Merve Hacer; Baybars, Sümeyye Coşgun (My University, 2024)
Aim: The aim of this study is to determine the types and incidence of soft tissue calcifications observed on panoramic radiographs of edentulous patients. Material and methods: A total of 1297 panoramic radiographs of edentulous patients who applied to Fırat University School of Dentistry for different reasons between 2013 and 2022 and had a consent form were evaluated retrospectively. 131 radiographs with magnification and positioning errors were not included. Calcifications were classified according to localization, number, structure, shape and appearance. IBM SPSS Statistics 22 program was used for statistical analysis. Compatibility of the parameters with normal distribution was evaluated with the Kolmogorov-Smirnov test. In addition to descriptive statistical methods; Mann-Whitney U, Chi-Square, Fisher's Exact Chi-Square, Kruskal Wallis tests and Continuity (Yates) Correction were used. Significance was evaluated at p<0.05. Results: A total of 1166 panoramic radiographs (539 female, 627 male) were examined and soft tissue calcifications were detected in 274 patients (23.5%). The ages of patients with calcification range from 36 to 88; 146 (53.3%) were male and 128 (46.8%) were female. The mean age was 64.45±9.06 years. Tonsillolith in 17.5%, carotid artery calcification in 10.6%, lymph node calcification in 4.8%, triticeous cartilage calcification in 2.1%, antrolith in 0.9%, rhinolith in 0.7%, sialolith in 0.4% and phleboliths were detected in only one patient (0.08%) of all cases. Conclusion: The diagnosis of soft tissue calcifications by dentists and their differentiation from anatomical structures and pathologies are very crucial. In this way, it is possible to prevent unnecessary examinations and treatments and also to refer patients for further examinations when necessary.
Keywords: Calcification; Edentulism Panoramic radiography